(untitled) (Anclajes, 2024)
For many homosexual men, coming to terms with their sexual orientation represents a complex process. It is interesting, in this sense, to establish how the rise of neoconservatism gave a particular aspect to the expressions of shame and pride associated with sexuality in general and, specifically, with the sexual identity of Mexican gay men. The references that will be used for the development of the research will be interviews carried out with Mexican gay men within the framework of the research project "Rural homosexual childhoods and adolescence", in which the intention was to understand the strategies used by homosexual men during their childhood to survive the contexts of homophobia in which they lived until reaching adulthood. The majority of the subjects, despite having explored their sexuality from a very young age alongside other boys from their communities of origin, managed to prevent their sexual orientation from triggering forms of violence or exclusion while they lived with their family.